2017
DOI: 10.3390/cancers9040031
|View full text |Cite
|
Sign up to set email alerts
|

NG2 Proteoglycan Enhances Brain Tumor Progression by Promoting Beta-1 Integrin Activation in both Cis and Trans Orientations

Abstract: By physically interacting with beta-1 integrins, the NG2 proteoglycan enhances activation of the integrin heterodimers. In glioma cells, co-localization of NG2 and α3β1 integrin in individual cells (cis interaction) can be demonstrated by immunolabeling, and the NG2-integrin interaction can be confirmed by co-immunoprecipitation. NG2-dependent integrin activation is detected via use of conformationally sensitive monoclonal antibodies that reveal the activated state of the beta-1 subunit in NG2-positive versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 76 publications
1
38
0
Order By: Relevance
“…Glycanated variants concentrate in filopodial extensions, including the finest protrusions conventionally denoted "microspikes," where they seem to colocalize with b1, a3, and a4 integrin subunits, ezrin, and neural precursor cell expressed, developmentally downregulated 9 ( Fig. 4 and Table 1) (17,23,(43)(44)(45)(46)(47). However, NG2/CSPG4 molecules lacking GAG chains have also been noted in microclustered configurations confined to putative lipid rafts.…”
Section: Subcellular Organization Of Ng2/cspg4 Glycoforms Is Dictatedmentioning
confidence: 97%
See 3 more Smart Citations
“…Glycanated variants concentrate in filopodial extensions, including the finest protrusions conventionally denoted "microspikes," where they seem to colocalize with b1, a3, and a4 integrin subunits, ezrin, and neural precursor cell expressed, developmentally downregulated 9 ( Fig. 4 and Table 1) (17,23,(43)(44)(45)(46)(47). However, NG2/CSPG4 molecules lacking GAG chains have also been noted in microclustered configurations confined to putative lipid rafts.…”
Section: Subcellular Organization Of Ng2/cspg4 Glycoforms Is Dictatedmentioning
confidence: 97%
“…4). Furthermore, in membrane microprotrusions, the intracellular domain of NG2/CSPG4 is preferentially phosphorylated in Thr 2314 by a PKCadependent mechanisms and this phosphorylation event seems crucial in directing the PG, along with integrin a3b1 (and possibly other b1-class integrins), into these cell membrane domains (43,44,47). Whether NG2/CSPG4, in its phosphorylated or unphosphorylated state, acts as a promoter of the cell membrane protrusion leading to formation of filopodial/invadopodial extensions would need to be defined by further investigations.…”
Section: Table 1 Summary Of the Molecular Interplays Exerted By Ng2/mentioning
confidence: 99%
See 2 more Smart Citations
“…The functional pathways of genes of which expression increased in CAFs of HER-2 positive breast cancer were actin cytoskeleton signaling and integrin signaling. It has been reported that actin cytoskeleton signaling is associated with NG2 [29] and PDGFR [30], while integrin signaling is associated with S100A4 [31][32][33] and NG2 [34][35][36]. It has also been reported that molecular features that induce disease progression are different in each intrinsic molecular subtype of DCIS [24] and have an important role in the tumor microenvironment and progression of DCIS [37,38].…”
Section: Discussionmentioning
confidence: 99%